The Beginning of the Road for Non-Coding RNAs in Normal Hematopoiesis and Hematologic Malignancies - Heuston, Elisabeth F. (Frontiers Research Foundation, 2011)
The field of non-coding RNAs (ncRNAs) encompasses a wide array of RNA classes that are indispensible for the regulation of cellular activities. However, de-regulation of these ncRNAs can also play key roles in malignant transformation and cancer cell behavior. In this article we survey a select group of microRNAs and long ncRNAs that appear to contribute in keys ways to the development of acute and chronic leukemias, as well as contribute to their diagnosis, prognosis, and potentially, their treatment.